Television market, ownership concentration and management strategies in Portugal. (1st June 2018) - Faustino, Paulo
The main objective of this article is to measure media concentration of the Portuguese television industry, and to evaluate the extension to which concentration in television companies relates to management strategies. A review of literature about media economics and management and strategic decisions is presented. Following this theoretical background, the empirical analysis of the ownership concentration of Portuguese television companies is based on qualitative and quantitative methods. The main information sources were corporate reports, television market reports, specialized books, articles and scientific papers, among other documental sources of information related to this area. In terms of main conclusions, high television ownership concentration levels, which have always been a feature of the Portuguese television industry market, although still high, have been decreasing for the past ten years. However, high concentration levels are observed in media groups, resulting from the convergence of television and other types of media. This is mainly due to bundling strategies of telecom operators (which added pay television services to the traditional telecommunications portfolio) and to diversification strategies from television network players (taking advantage of audience segmentation and easier access to broadcasting space).